Carpenter and builders library No. 2 : builders math, plans, specifications - Ulrey, Harry F. (Indiana Theodore Audel & Co, 1970)
This text gives a detailed explanation of the mathematics needed by the carpenter. surveying as it pertains to the builder is covered at length along with a coverage of practical drawing.
Includes bibliographical references and index.
ijb 17/01/2019
Loans
Keywords: Craftmanship; Woodwork; Carpenter and builders; Builders math